2009
DOI: 10.1016/j.pain.2008.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Colon mustard oil instillation induced cross-organ reflex sensitization on the pelvic–urethra reflex activity in rats

Abstract: We investigated the participation of cyclin-dependent kinase-5 (Cdk5)-mediated N-methyl-D-aspartate receptor (NMDAR) NR2B subunit phosphorylation in cross-organ reflex sensitization caused by colon irritation. The external urethral sphincter electromyogram (EUSE) reflex activity evoked by the pelvic afferent nerve test stimulation (TS, 1 stimulation/30s) and protein expression in the spinal cord and dorsal root ganglion tissue (T13-L2 and L6-S2 ipsilateral to the stimulation) in response to colon mustard oil (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
34
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 78 publications
2
34
0
Order By: Relevance
“…The right lumbosacral (L6 -S2) dorsal horns were dissected out and were immediately snap-frozen on liquid nitrogen. The protocol for Western blotting has been described elsewhere (22,23); in brief, the sample was homogenized and the extracts were centrifuged to retain supernatants. The supernatant was separated on an acrylamide gel and transferred to a polyvinylidene difluoride membrane and then were incubated for 1 h at room temperature in either rabbit antiephrinB2 (1:2,000, Santa Cruz Biotechnology), anti-phosphorylated EphB1/2 (pEphB1/2l 1:2,000, Millipore), rabbit anti-phospho-Src antibody (1:1,000, Millipore), or rabbit anti-phosphotyr1336 or anti-phosphotyr1472-NR2B (1:1,000 Millipore).…”
Section: Western Blottingmentioning
confidence: 99%
See 1 more Smart Citation
“…The right lumbosacral (L6 -S2) dorsal horns were dissected out and were immediately snap-frozen on liquid nitrogen. The protocol for Western blotting has been described elsewhere (22,23); in brief, the sample was homogenized and the extracts were centrifuged to retain supernatants. The supernatant was separated on an acrylamide gel and transferred to a polyvinylidene difluoride membrane and then were incubated for 1 h at room temperature in either rabbit antiephrinB2 (1:2,000, Santa Cruz Biotechnology), anti-phosphorylated EphB1/2 (pEphB1/2l 1:2,000, Millipore), rabbit anti-phospho-Src antibody (1:1,000, Millipore), or rabbit anti-phosphotyr1336 or anti-phosphotyr1472-NR2B (1:1,000 Millipore).…”
Section: Western Blottingmentioning
confidence: 99%
“…At the lumbosacral spinal cord, our laboratory has recently demonstrated a novel form of pain-related central sensitization, cross-organ sensitization, in which instillation of mustard oil (MO) into the descending colon could sensitize the reflex activity of the urethra (21,22). Pharmacological investigations indicated spinal NR2B subunit phosphorylation is crucial in the induction of cross-organ sensitization (19,20,23).…”
mentioning
confidence: 99%
“…In the last decade, studies have demonstrated that the interactions between EphBRs and their ephrinB ligands modulate neural plasticity induction in the mammalian central nervous system, mainly, but not exclusively, via exhibiting effects on NMDAR (8,12). A recent study also demonstrated that, in association with thermal hyperalgesia, EphBR activation caused by immunoglobulin fusion protein of ephrinB2 (ephrinB2-Fc)-induced, Src kinase-dependent NR2B phosphorylation in the spinal cord (2), suggesting that ephrinB2-EphBR tyrosine kinase interactions could probably modulate pain signaling via spinal Src-dependent NMDAR phosphorylation (2).Although further proof is still needed for the physiological and/or pathophysiological relevance, the induction of pelvicurethra reflex potentiation (15, 16), a form of NR2B phosphorylation-dependent neural plasticity (5,25,31,41), has been linked to the development of visceral pain from pelvic organs (26,27,30,32,33). Studies have shown that the activation of nociceptive afferent fibers expressing transient receptor potential vanilloid/transient receptor potential ankyrin by the instillation of irritants into the uterus (32, 33) and the descending colon (29) facilitated pelvic-urethra reflex activity in a crossorgan manner.…”
mentioning
confidence: 99%
“…Although further proof is still needed for the physiological and/or pathophysiological relevance, the induction of pelvicurethra reflex potentiation (15, 16), a form of NR2B phosphorylation-dependent neural plasticity (5,25,31,41), has been linked to the development of visceral pain from pelvic organs (26,27,30,32,33). Studies have shown that the activation of nociceptive afferent fibers expressing transient receptor potential vanilloid/transient receptor potential ankyrin by the instillation of irritants into the uterus (32, 33) and the descending colon (29) facilitated pelvic-urethra reflex activity in a crossorgan manner.…”
mentioning
confidence: 99%
“…Cross-sensitization between the bladder and other pelvic viscera is a clinical concern that makes diagnosing and treating the etiology difficult (Berkley, 2005, Baranowski et al, 2008, Theoharides et al, 2008, van de Merwe et al, 2008. In humans and in animals, the organs that seem to be most often involved in pelvic cross-sensitization besides bladder and colon, with respect to spinal afferents, appear to be the pelvic urethra and the uterus (Dmitrieva et al, 2001, Giamberardino et al, 2001, Dmitrieva and Berkley, 2002, Morrison et al, 2006, Peng et al, 2008a, Peng et al, 2008b, Peng et al, 2009). …”
Section: Electrophysiological Properties Of Ng Neuronsmentioning
confidence: 99%